2010
DOI: 10.1542/peds.2009-3445
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Tracheal Aspirate Mesenchymal Stromal Cells Predicts Bronchopulmonary Dysplasia

Abstract: Background We have isolated mesenchymal stromal cells (MSCs) from tracheal aspirates of premature infants with respiratory distress. Under the influence of transforming growth factor-β, MSCs differentiate into α-smooth muscle actin-expressing myofibroblasts. Myofibroblasts are increased in the lungs of patients with bronchopulmonary dysplasia (BPD), a chronic lung disease of prematurely-born infants. Objective We tested whether isolation of MSCs from tracheal aspirates of premature infants with respiratory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 30 publications
6
64
0
Order By: Relevance
“…Thin black lines signify 1.5-fold change based on average probe signal. BPD at a significantly higher rate than patients from whom these cells were not isolated [9]. In the present study, study subjects again demonstrated a high prevalence of BPD; 60% developed BPD, compared with the reported 25% of very low birth weight premature infants [1].…”
Section: Figsupporting
confidence: 56%
See 3 more Smart Citations
“…Thin black lines signify 1.5-fold change based on average probe signal. BPD at a significantly higher rate than patients from whom these cells were not isolated [9]. In the present study, study subjects again demonstrated a high prevalence of BPD; 60% developed BPD, compared with the reported 25% of very low birth weight premature infants [1].…”
Section: Figsupporting
confidence: 56%
“…Our laboratory has previously isolated plastic-adherent, fibroblast-like cells from the tracheal aspirates of premature infants undergoing mechanical ventilation for respiratory distress [7][8][9]. These cells possess colony-forming potential, surface markers, and differentiation potential typically found in mesenchymal stem cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[55][56][57][58] However, airway-derived MSCs are increased in BPD, suggesting that the tissue of origin (e.g., blood, vascular endothelial wall, bone marrow, airway epithelium) plays a critical and yet undefined role in the pathogenesis of BPD. 59 Further studies are needed to describe more clearly how progenitor cell-mediated vasculogenesis is disrupted to cause PVD in BPD and whether progenitor cell therapy will prevent or treat cardiopulmonary disease in preterm infants. Small clinical trials with the most severely affected neonates are the most likely setting in which such novel therapies will be translated into clinical practice.…”
Section: Pathophysiology Of Ph In Bpdmentioning
confidence: 99%